Magnetic field detection in the bright A0-type supergiant HD 92207 - Hubrig, S. (2012)
Context. Recent developments in observational techniques and theories revealed the potential significance of magnetic fields for stellar structure, evolution, and circumstellar environment. At present, the distribution of magnetic field strengths in massive stars from the zero-age main sequence to more evolved stages, which would shed light on the origin of the magnetic field, has not been studied. Aims. We searched for the presence of a magnetic field in the visually brightest early A-type supergiant HD 92207. Methods. Observations were obtained using the low-resolution spectropolarimetric mode of FORS 2 (FOcal Reducer low dispersion Spectrograph) mounted on the 8 m Antu telescope of the VLT. For the mean longitudinal magnetic field measurements, we applied a linear regression analysis in two ways: using only the absorption hydrogen Balmer lines or using the entire spectrum including all available absorption lines. Results. A mean longitudinal magnetic field at a significance level of more than 3σ was detected in two out of three observations distributed over about one year. It is one of the rare cases where a field of about a few hundred Gauss is detected in an early A-type supergiant. All line profiles in the spectra of HD 92207 undergo distinct variations in radial velocities and intensities, probably caused by previously detected non-radial pulsations.